Amphiphilic core-cross-linked micelles functionalized with bis(4-methoxyphenyl)phenylphosphine as catalytic nanoreactors for biphasic hydroformylation. (18th August 2015) - Chen, Si; Cardozo, Andrés F.; Julcour, Carine; Blanco, Jean-François; Barthe, Laurie; Gayet, Florence; Lansalot, Muriel; D'Agosto, Franck; Delmas, Henri; Manoury, Eric; Poli, Rinaldo
Abstract: Core-cross-linked micelles (CCM) functionalized at the core with covalently linked bis( p -methoxyphenyl) phenylphosphine (BMOPPP) ligands have been synthesized by a three-step one-pot radical polymerization in emulsion, using the polymerization-induced self-assembly (PISA) strategy and reversible addition-fragmentation chain transfer (RAFT) as the controlling method. The CCM are obtained by chain extending in water poly(methacrylic acid- co -poly(ethylene oxide) methyl ether methacrylate) (P(MAA- co -PEOMA), degree of polymerization of 30, MAA/PEOMA units molar ratio of 50:50) synthesized in a first step by RAFT with a 95:5 M mixture of styrene and 4-[bis( p -methoxyphenyl)phosphino]styrene (BMOPPS) units. The resulting micelles exhibiting a core composed of P(S- co -BMOPPS) segments with a degree of polymerization of 300 are then crosslinked in a third step with a mixture of di(ethylene glycol) dimethacrylate (DEGDMA) and styrene. The resulting BMOPPP@CCM exhibit a narrow size distribution (PDI = 0.16) with an average diameter of 81 nm in water and swell in THF or by addition of toluene to the latex. The addition of [Rh(acac) (CO)2 ] to the toluene-swollen latex results in metal coordination to the phosphine ligands. 31 P 1 H NMR spectroscopy shows that the Rh centers undergo rapid intraparticle phosphine ligand exchange. Application of these nanoreactors to the aqueous biphasic hydroformylation of 1-octene shows excellent activity and moderate catalyst leaching. Graphical abstract: Highlights: New phosphine-ligand-functionalized core-cross-linked micelles. Polymerization-induced self-assembly of amphiphilic core-shell polymers by RAFT. Efficient biphasic hydroformylation of 1-octene.